A massive haemorrhage developing during deciduous tooth extraction in a young child: A case report. (2017) - Bocchialini, Gabriele; Ferrari, Luca; Burlini, Dante
Highlights: Various evidence-based guidelines for dental clinicians deal with the use of general anaesthesia when treating children. Management of acute haemorrhage can be difficult and the decision of how to manage a severe acute haemorrhage is influenced by many factors. we had identified the patient as a "fragile child'; our protocol dictated that she should be treated in the operating room. This meant that, when the emergency developed, we had everything that we needed to hand. Abstract: Introduction: Major haemorrhage developing during oral or maxillofacial surgery is uncommon, but potentially life-threatening. Dental extractions in childhood are common, but blood loss is unusual. Case presentation: Here, we report a rare case of a complication developing during a trivial deciduous tooth extraction. We focus on the great difference between the preoperative orthopantomography and the maxillo-facial computed tomography obtained post-haemorrhage. Discussion: The surgical procedures most commonly associated with acute haemorrhage are orthognathic, oncological, and temporomandibular joint procedures. When acute haemorrhage develops, the surgeon must remain calm, temporarily arrest the bleeding, and ultimately definitively control it. Although ligation of the offending artery, vein, or vascular malformation is clearly the treatment of choice, identifying the offending vessel and gaining adequate access thereto are often difficult. Conclusion: We emphasise that what we encountered could happen in routine daily practice.